Karakteristik Pewarna Alami Cair Terbuat dari Variasi Rasio Tepung Labu Kuning (Cucurbita moschata): Pelarut dan Lama Waktu Ekstraksi: Characteristic of Liquid Natural Colorant Made from Variations in The Ratio of Yellow Pumpkin Flour: Solvent and Extraction Time - Nafi', Ahmad; Yuwanti, Sih; Fahmi, Dafiq Kurniawan; Subagio, Achmad; Diniyah, Nurud (Faculty of Agricultural Technology, University of Jember, 2024)
Liquid natural colorant is an alternative product which was produced from pumpkin flesh. The pumpkin contains high carotenoid compounds which rich of antioxidants. This research was aimed to determine the effect of solvent concentration and extraction time on the characteristics of liquid natural colorant from pumpkin. This study used a completely randomized design with two factors, namely the ratio of yellow pumpkin flour: solvent (1:6, 1:8, and 1:10 (w/v)) and extraction time (1, 2, and 3 days). Each treatment was repeated three times. Based on the results of the research, the treatment with a ratio of yellow pumpkin flour: solvent (w/v) 1:10 and the extraction time is 3 days produced the best liquid natural colorant, with the characteristics: brightness level (lightness) was 85.59 of lightness, 85.17% of antioxidant activity, 3.94 mg GAE/mL of total polyphenol, 0.63 mg/100 g of carotenoid content, the color stability test based on temperature storage (room temperature and cold temperature), respectively 2.96 and 3.42, and color stability test based on light intensity (lamp light and covered with aluminum foil) 2.79 and 2.84, respectively. According to these findings, the maceration method used on this research could be applied on production of natural colorant made from yellow pumpkin. Keywords: extraction time, liquid natural colorant, solvent, yellow pumpkin